THE RESULTS OF SURGICAL TREATMENT OF PATIENTS WITH ACTIVE TUBERCULOUS SPONDYLITIS - Golka, G.G.; Vesnin, V.V.; Burlaka, V.V.; Oliinyk, A.O.; Fadeev, O.G.; Litvishko, V.O.; Frolova-Romaniuk, E.Y. (World of Medicine and Biology, 2022)
The analysis of the treatment of 60 patients with active TS was performed. The main group (n=30) includes patients with lesions of the thoracic and lumbar vertebrae, operated using a telescopic titanium cage for ventral interbody spondylodesis after necrosequestrectomy. A feature of preoperative preparation of patients of the main group was the mandatory etiological diagnosis before treatment, the appointment of a short preoperative course of specific antibacterial therapy, taking into account the results of etiological diagnosis for 2–3 weeks, followed by surgery. The control group included patients (n=30) using traditional approaches to treatment – preoperative preparation using 3–5 specific antibacterial drugs without determining the sensitivity for 2–3 months, followed by surgery – decompressive necrectomy of the affected vertebrae and anterior spondylodesis using an autograft. In the comparative analysis of short-term and long-term results of surgical treatment of patients of both groups, the results were obtained, which clearly showed the high clinical effectiveness of the proposed method of treatment of patients of the main group using modern advances in vertebrology.
Keywords: specific tuberculous lesions of the spine; improvement of surgical treatment